Pengaruh Inflasi, Pengangguran, Kemiskinan, Dan Pembiayaan Perbankan Terhadap Pertumbuhan Ekonomi Di Indonesia - Hidayatullah, Muhammad Suib; Rosyidah, Norma; Saifuddin, Saifuddin (International Conference on Islamic Economic (ICIE), 2023)
One important aspect of national development is the development of a country with the ultimate goal of improving people's welfare. This happened in Indonesia. So, research should be carried out to find out what are the obstacles hindering Indonesia's economic growth. The purpose of this study is to find out how inflation, unemployment, poverty, Islamic banking financing affect Indonesia's economic growth partially and simultaneously. This study uses secondary information arranged in chronological order from 2014 to 2022. This information was obtained from the official websites of Bank Indonesia, the Central Bureau of Statistics and OJK. The independent variables in this study are inflation, unemployment, poverty, and Islamic banking financing, while the dependent variable is economic growth. This study uses multiple regression analysis, T-test, coefficient of determination, and F-test. The results of the research show that inflation, unemployment, poverty, bank financing simultaneously affect Indonesia's economic growth by 65.2%. Other variables not included in this study affect the remaining 34.8%.